The contribution of hydroxylamine content to spatial variability of N2O formation in soil of a Norway spruce forest. (1st April 2016) - Liu, Shurong; Herbst, Michael; Bol, Roland; Gottselig, Nina; Pütz, Thomas; Weymann, Daniel; Wiekenkamp, Inge; Vereecken, Harry; Brüggemann, Nicolas
Abstract: Hydroxylamine (NH2 OH), a reactive intermediate of several microbial nitrogen turnover processes, is a potential precursor of nitrous oxide (N2 O) formation in the soil. However, the contribution of soil NH2 OH to soil N2 O emission rates in natural ecosystems is unclear. Here, we determined the spatial variability of NH2 OH content and potential N2 O emission rates of organic (Oh) and mineral (Ah) soil layers of a Norway spruce forest, using a recently developed analytical method for the determination of soil NH2 OH content, combined with a geostatistical Kriging approach. Potential soil N2 O emission rates were determined by laboratory incubations under oxic conditions, followed by gas chromatographic analysis and complemented by ancillary measurements of soil characteristics. Stepwise multiple regressions demonstrated that the potential N2 O emission rates, NH2 OH and nitrate (NO3 − ) content were spatially highly correlated, with hotspots for all three parameters observed in the headwater of a small creek flowing through the sampling area. In contrast, soil ammonium (NH4 + ) was only weakly correlated with potential N2 O emission rates, and was excluded from the multiple regression models. While soil NH2 OH content explained the potential soil N2 O emission rates best for both layers, also NO3 − and Mn content turned out to be significant parameters explaining N2 O formation in both soil layers. The Kriging approach was improved markedly by the addition of the co-variable information of soil NH2 OH and NO3 − content. The results indicate that determination of soil NH2 OH content could provide crucial information for the prediction of the spatial variability of soil N2 O emissions.